PENERAPAN HANDOUT ELEKTRONIK BERBASIS CANVA TERHADAP PEMBELAJARAN MENGANALISIS TEKS EKSPOSISI KELAS VIII - Ismi Saumi Alawiah; Eli Syarifah Aeni; Restu Bias Primandhika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
21st century learning has criteria that integrate with technology. One of the efforts to use technology in learning is to use teaching materials. Electronic teaching materials can be an alternative for educators, students, and schools. Its flexible nature makes it easier for learning activities. The This study's goals were to: (1) describe how electronic handouts are used with exposition text content and (2) determine whether using electronic handouts helps students learn exposition texts. In this inquiry, the descriptive qualitative method was used information gathered by answering a questionnaire. The study's conclusions suggest that electronic handouts made with Canva are useful for studying exposition materials. This was obtained through the results of a questionnaire, namely as many as 91.2% of students agreed and strongly agreed on the usefulness of Canva-based electronic handouts in analyzing exposition texts.